Damon Galgut and the critical reception of South African literature - Kostelac, Sofia Lucy (My University, 2014)
Damon Galgut has been a prolific contributor to South African literature since the early 1980s, but has only recently gained recognition as a significant presence in our cultural landscape. This thesis considers what the vicissitudes of Galgut’s critical reception — which have seen him, by turns, celebrated, ignored and even explicitly discounted as a noteworthy South African author — reveal about the shifting standards of cultural legitimacy which have been set for local writers since the late apartheid years. It offers, in turn, an extended close reading of each of his novels and considers the challenges which they pose to hegemonic assumptions about developments within the field of South African literature over the past three decades. I demonstrate that no coherent line of transition can be traced across the individual novels which make up Galgut’s oeuvre. They represent, instead, shifting degrees of discordance and concordance with an epochal metanarrative of South African literature and the progressive transformation of the field which it implies. In so doing, they enliven us to the thematic and aesthetic heterogeneity which has always already constituted the field.
Keywords: Damon Galgut; South African literature; Authorship; Critical reception